Seasonal antibacterial activity of two red seaweeds, Palmaria palmata and Grateloupia turuturu, on European abalone pathogen Vibrio harveyi. Issue 2 (16th December 2014) - García-Bueno, Nuria; Decottignies, Priscilla; Turpin, Vincent; Dumay, Justine; Paillard, Christine; Stiger-Pouvreau, Valérie; Kervarec, Nelly; Pouchus, Yves-François; Marín-Atucha, Arnaldo Aitor; Fleurence, Joël
<x content-type="archive" xml:space="preserve">Abstract</x> Vibrio harveyi is the main pathogen of the European abalone Haliotis tuberculata, and recently caused important mortalities at the production sites of this marine gastropod in France. In the present work, the monthly antibacterial activity of two red seaweed species from the French Atlantic coast, the native Palmaria palmata and the introduced Grateloupia turuturu, were investigated against the abalone pathogen Vibrio harveyi strain ORM4. Water-soluble extracts were screened using the microplate method. Grateloupia turuturu showed an antibacterial activity with a maximal growth inhibition in spring of around 16%. In contrast, Palmaria palmata was inactive, as further growth of the bacteria was observed. Preliminary one-dimensional proton nuclear magnetic-resonance (1H NMR) profiles identified the differences between the two water-soluble extracts.